IMPLEMENTASI MODEL PROJECT BASED LEARNING PADA MATERI MEMBUAT POSTER DALAM PEMBELAJARAN BAHASA INDONESIA DI KELAS IX SMP NEGERI 2 ANGGERAJA KABUPATEN ENREKANG - Aulia Syahrani; Mayong; Aswati Asri (STKIP Subang, 2026)
This research aims to describe the implementation of the Model Project Based Learning (PjBL) on the material to make posters in Indonesian language learning in class IX SMP Negeri 2 Anggeraja Enrekang Regency. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The focus of research covers the planning, implementation, and evaluation stages of learning. The results showed that in the planning stage, teachers have compiled a systematic learning tools in accordance with the syntax of PjBL, including teaching modules, worksheets learners (LKPD), as well as instruments and rubric assessment of the project. In the implementation phase, learning takes place in an active and student-centered manner through poster making project activities that involve student cooperation and creativity. Furthermore, in the evaluation stage, the teacher assesses the process and results of the project and gives students the opportunity to reflect on the learning experience gained. Based on the findings of this study, it can be concluded that the implementation of the Project-Based Learning (PjBL) model in poster-making activities was carried out effectively and successfully enhanced students' active participation, creativity, collaboration skills, and engagement in Indonesian language learning.